Analisis Strategi Dakwah Pengurus Masjid Al-Firdaus dalam Menghadapi Era Society 5.0 - Santi Dianah; Sausan M. Sholeh (Jurnal Riset Komunikasi Penyiaran Islam, 2022)
Abstract. The presence of Era Society 5.0 creates new habits in the use of technology as problem solving in all aspects of life to provide convenience for the community, including in overcoming religious problems. This era of Society 5.0 forced masjid to carry out tajdid (renewal) movements. Masjid are required to be more transformative, responsive, adaptive and able to answer increasingly complex da'wah problems. Based on this phenomenon, the problems in this study are formulated as follows: (1). How do the administrators of Masjid Al-Firdaus, Pangalengan District understand about Era Society 5.0? (2). What are the factors that influence the implementation of the da’wah strategy of the administrators of Masjid Al-Firdaus, Pangalengan District in facing the Era of Society 5.0? (3). How is the da’wah strategy of the administrators of Masjid Al-Firdaus in Pangalengan District in the face of the Era of Society 5.0 ?. The research was conducted using a descriptive method with a qualitative approach. Informants selected in this study were masjid’s pioneers, masjid’s administrators, masjid’s congregations, beneficiaries of masjid social activities, and local RT heads. Data collection techniques used in this study were observation, interviews, and literature study. The data analysis techniques used in this study include data collecting, data reduction, data display, and conclusion. The results of this study are: There are three strategies carried out by the administrators of masjid in facing the Era of Society 5.0, namely carrying out the masjid digitization movement, increasing social activities, and collaborating with other organizations. Abstrak. Hadirnya Era Society 5.0 menimbulkan kebiasaan baru dalam penggunaan teknologi sebagai problem solving pada semua aspek kehidupan untuk memberikan kemudahan bagi masyarakat, termasuk dalam mengatasi masalah keagamaan. Era Society 5.0 ini memaksa masjid untuk melakukan gerakan tajdid . Masjid dituntut untuk lebih transformatif, responsif, adaptif dan mampu menjawab persoalan dakwah yang semakin kompleks. Bagaimana pemahaman pengurus Masjid Al-Firdaus Kecamatan Pangalengan mengenai Era Society 5.0 ? . Apa faktor yang mempengaruhi pelaksanaan strategi dakwah pengurus Masjid Al-Firdaus Kecamatan Pangalengan dalam menghadapi Era Society 5.0 ? . Bagaimana strategi dakwah pengurus Masjid Al-Firdaus Kecamatan Pangalengan dalam menghadapi Era Society 5.0 ?. Informan yang dipilih dalam penelitian ini adalah perintis masjid, pengurus masjid, jama’ah masjid, penerima manfaat kegiatan sosial masjid, dan ketua RT setempat. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah observasi, wawancara, dan studi literatur. Adapun teknik analisis data yang digunakan dalam penelitian ini meliputi data collecting, data reduction, display data, dan conclusion.